Avaliação de meios filtrantes com diferentes técnicas de fabricação em filtros de mangas - Peroni, Bárbara Leticia (2022)
Air pollution by particulate matter has been the subject of study by many researchers, where they report that these particles can penetrate through the bloodstream causing serious health problems. To reduce the negative effects of these processes on air quality, industries need to look for some alternatives to remove or reduce the amount of particulate matter to be released into the atmosphere. The bag filter is an equipment composed of non-woven (nonwven) filter elements, which aims to control the emission of these particles. This fabric, which forms the filter medium, varies according to the particulate material to be filtered, in order to have a high efficiency in the retention of the particles along with a low operating cost. Filter media for very fine particles have a high cost, making it necessary, to reduce the operational cost of the process, to choose the most suitable filter media for that operation. With that in mind, the present work aims to evaluate 100% meta-aramid filter media with different manufacturing techniques, one needled and the other hydroblasted. The purpose is to identify the most suitable filter medium to be used in the process of filtering gases in a bag filter in the secondary dedusting stage of pig iron desulfurization in a steel industry. For this, initially the characterization of the particulate material was carried out (granule distribution, density and composition), later, the characterization of virgin filter media (porosity, permeability, fiber diameter, permeability and thickness). The filtration tests performed were according to the VDI 3926 standard, which evaluated the collection efficiency for nano and microparticles, for the first and thirty filtration cycles. With the results obtained, it is shown that the gaps left by the needles during the fabrication process of the needled filter media, become preferential air paths and thus having greater permeability and porosity. It was also verified that for the thirty filtration cycles the virgin needled and hydroblasted filter media showed efficiency of close collections, but the filtration time of the hydroblasted filter medium was shorter than the needled filter medium, to reach the maximum pressure. After aging, there was a reduction in permeability and filtration time of both filter media. However, the hydroblasted filter media showed longer filtration time and efficiency than the needled filter media.